Polemik negara Islam : Soekarno versus Natsir - Suhelmi, Ahmad, 1962- (Jakarta : Penerbit Universitas Indonesia, 2012)
Issues on the concept of an Islamic state in Indonesia; criticism on polemical thougts of Soekarno and Natsir, Indonesian politicians.
'Edisi revisi, dilengkapi perdebatan tentang negara Islam menurut Islam liberal dan Islam literal.'
Keywords: Soekarno, -- 1901-1970 -- Religion; Natsir, M., -- 1908-1993 -- Religion; Islam and state -- Indonesia; Islam and politics -- Indonesia